Permanent magnet variable flux sources. - COEY, JOHN MICHAEL DAVID (IEEE, 1994)
Rotatable transversely-magnetized permanent magnet rods can be used to generate variable, uniform magnetic fields or field gradients. A four-rod device for use at the specimen stage of an optical microscope is described where the field can be in-plane or perpendicular to the stage. The maximum flux density ranges from 36 mT (360 G) for isotropic ferrite to 210 mT (2.1 kG) For sintered Nd-Fe-B. Calculated and measured field profiles are in good agreement. Homogeneity is better than 1% of maximum in a region of diameter 7 mm or 3.5 mm at maximum and zero field, respectively
PUBLISHED
Keywords: Physics